Potential Diagnostic Biomarkers: Differential Expression of LMP2/β1i and Cyclin B1 in Human Uterine Leiomyosarcoma. Issue 4 (July 2014) - Hayashi, Takuma; Horiuchi, Akiko; Sano, Kenji; Hiraoka, Nobuyoshi; Ichimura, Tomoyuki; Sudo, Tamotsu; Ishiko, Osamu; Yaegashi, Nobuo; Aburatani, Hiroyuki; Konishi, Ikuo
Aims and Background: Whilst most uterine smooth muscle neoplasms are benign, uterine leiomyosarcoma (Ut-LMS) is extremely malignant with a high incidence of metastasis and recurrence. Gynecological tumors are often associated with female hormone secretion, but no strong link has been detected between human Ut-LMS and the hormonal environment. In fact, the risk factors for Ut-LMS are poorly understood. In addition, no diagnostic biomarkers for differentiating between leiomyoma, a benign tumor, and malignant Ut-LMS have been found. Interestingly, mice that were homozygously deficient for LMP2/β1i were found to spontaneously develop Ut-LMS and exhibited a Ut-LMS prevalence of 40% by 14 months of age. Thus, analyzing potential risk factors for Ut-LMS (such as LMP2/β1i) might aid the development of diagnostic biomarkers and clinical treatments for the condition. Methods and Study Design: Fifty-seven patients (age range: 32–83 years) who had been diagnosed with uterine mesenchymal tumors were chosen from a pathological archive. Tissue samples from these patients were fixed in 10% buffered formalin, incubated in 4% paraformaldehyde for 8 hours, and embedded in paraffin. Tissue sections were stained with hematoxylin and eosin for standard histological examination or were subjected to further processing for immunohistochemical (IHC) examination. Serial Ut-LMS, bizarre leiomyoma, leiomyoma, and myometrium sections were subjected to IHC staining of β-smooth muscle actin, estrogen receptor, cyclin B1, LMP2/β1i, calponin h1, ki-67, tumor protein p53, and progesterone receptor. Results: The Ut-LMS samples were positive for cyclin B1 and negative for LMP2/β1i, while the opposite result was obtained for bizarre leiomyoma, leiomyoma, and myometrium samples. Conclusions: The expression pattern of LMP2/β1i and cyclin B1 might be a diagnostic biomarker for human Ut-LMS. Studies of the biological roles of LMP2/β1i and/or cyclin B1 could lead to the elucidation of new targets for therapies against Ut-LMS.